Synthesis of MgO/ZnO nanocomposites by flame spray pyrolysis - T. Samerjai (2018)
Flame Spray Pyrolysis (FSP) was used to synthesize MgO/ZnO nanocomposites with different MgO doping levels ranging from 5-20 wt%MgO. Zinc naphthenate and magnesium acetate tetrahydrate dissolved in ethanol were used as Zn and Mg precursors, respectively. The phase and crystallinity were analyzed by X-ray diffraction (XRD). The high specific surface area (SSABET) of the nanocomposites was measured by nitrogen adsorption (BET analysis). The sizes and morphologies of the nanocomposites were further investigated by transmission electron microscopy (TEM). The crystallite sizes of ZnO spheroidal and hexagonal particles were found to be ranging from 5-20 nm. XRD patterns revealed the MgxZn1-xO nanocomposite structure with 0.1<x<0.2. The average crystallite size of MgxZn1-xO spheroidal nanocomposite were in the range of 10-30 nm. MgxZn1-xO were nanorods were found to be ranging from 5-15 nm in width and 15-30 nm in length. The elemental compositions of the doping samples were ananlyzed by EDS line scan mode. © 2009 Amrican Institute of physics.